PENGARUH KESADARAN LINGKUNGAN PADA NIAT BELI PRODUK HIJAU: STUDI PERILAKU KONSUMEN BERWAWASAN LINGKUNGAN - Junaedi, M.F. Shellyana (Benefit, 2005)
This study examined the causal effect of the existing relationship between green purchasing, whichis attitudinal and behavioral approaches, environment consciousness, price premium, involvement andintention to green purchase. The idea implied on this research will help much in resolving problem anddecision making connected to reinforce the green purchase intention. The finding implied that environment consciousness influences to price premium and consumer involvement significantly. Another finding concludesthat consumer involvement significantlyinfluence to green purchase intention. Result, based on path analysis using AMOS indicated that the model tested had an acceptable fit. The goodness-of-fit index (GFI)was 0.977 which control for degree of freedom 1. Root mean square residual (RMR) was 0.009. The implicationof this research is relevant to marketers operating in organic-product market.